K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

12 tháng 12 2015

a) lx+3l:2=4

lx+3l=4.2=8

=> x+3=±8

 

TH1: x+3=8                    TH2: x+3=-8

        x=8-3=5                         x=(-8)-3=-11

b) l3x-3l:4=3

     l3x-3l=3.4=12

=> 3x-3=±12

TH1: 3x-3=12               TH2: 3x-3=-12

        3x=12+3=15                3x=(-12)+3=-9

         x=15:3=5                    x=(-9):3=-3

c) lxl=3

=> x=±3

Tick nha

12 tháng 12 2015

a)|x+3|:2=4

|x+3|=4.2

|x+3|=8

|X|=8-3

|x|=5

=>x=5 hoặc x=-5

b)|3x-3|:4=3

|3x-3|=3.4

|3x-3|=12

|3x|=12+3

|3x|=15

|x|=15:3

|x|=5

=>x=5 hoặc x=-5

c)|x|=3

=>x=3 hoặc x=-3

29 tháng 12 2021

c: \(\Leftrightarrow6x+3=\dfrac{11}{4}\left(2-x\right)\)

\(\Leftrightarrow x=\dfrac{10}{11}\)

3 tháng 1 2023

a,3/4 . (-5/12)+3/4.(-7/12)

` 3/4 . [ - ( 5/12 + 7/12  ) ] `

`3/4 . (-1) = -3/4 `

 

`2/3 . x - 0,5 = 3/4 `

 

`        x - 0,5 = 3/4 - 2/3 `

 

`        x-0,5 = 1/12 `

 

`        x =       1/12 + 0,5 `

 

`        x= 7/12 `

3 tháng 1 2023

a, 3/4 . (-5/12)+3/4.(-7/12) 

= 3/4 . [(-5/12) + (-7/12)]

= 3/4 . (-1)

= -3/4

----------------------------------------------------------------------------

a, 2/3 .x-0,5=3/4

2/3 . x = 3/2 + 0,5

2/3 . x = 2 

x = 2 : 2/3

x = 3 

vậy x = 3

 

Bài 2:

a: =>2/3x=3/4+1/2=3/4+2/4=5/4

=>x=5/4:2/3=5/4*3/2=15/8

b:=>-2x+4=3x-12

=>-5x=-16

=>x=16/5

4 tháng 5 2021

`c)1/4x+2/5=7/5`

`=>1/4x=7/5-1/5=1`

`=>x=1:1/4=4`

Vậy `x=4` 

4 tháng 5 2021

`a)2x-2/3=-3/4`

`=>2x=-3/4+2/3=-1/12`

`=>x=-1/24`

Vậy `x=-1/24`

 

8 tháng 12 2021

A

29 tháng 3 2022

A)    \(x-\dfrac{2}{3}=\dfrac{4}{5}\\ x=\dfrac{4}{5}+\dfrac{2}{3}\)

           \(x=\dfrac{22}{15}\)

b)\(\dfrac{7}{9}-x=\dfrac{1}{3}\\ x=\dfrac{7}{9}-\dfrac{1}{3}\\ x=\dfrac{4}{9}\)

C)\(x:\dfrac{2}{3}=\dfrac{9}{8}\\ x=\dfrac{9}{8}x\dfrac{2}{3}\\ x=\dfrac{3}{4}\)

 

 

29 tháng 3 2022

Câu D đâu bạn:)?

 

31 tháng 10 2021

\(a,\Rightarrow4x^2-20x-4x^2+3x+4x-3=5\\ \Rightarrow-13x=8\Rightarrow x=-\dfrac{8}{13}\\ b,\Rightarrow3x^2-10x+8-3x^2+27x=-3\\ \Rightarrow17x=-11\Rightarrow x=-\dfrac{11}{17}\\ c,\Rightarrow\left(x+3\right)\left(2-x\right)=0\Rightarrow\left[{}\begin{matrix}x=-3\\x=2\end{matrix}\right.\\ d,\Rightarrow2x\left(4x^2-25\right)=0\\ \Rightarrow2x\left(2x-5\right)\left(2x+5\right)=0\Rightarrow\left[{}\begin{matrix}x=0\\x=\dfrac{2}{5}\\x=-\dfrac{2}{5}\end{matrix}\right.\\ e,Sửa:\left(4x-3\right)^2-3x\left(3-4x\right)=0\\ \Rightarrow\left(4x-3\right)^2+3x\left(4x-3\right)=0\\ \Rightarrow\left(4x-3\right)\left(7x-3\right)=0\Rightarrow\left[{}\begin{matrix}x=\dfrac{3}{4}\\x=\dfrac{3}{7}\end{matrix}\right.\)

31 tháng 10 2021

a.

4x(x-5) - (x-1)(4x-3)-5=0

 4x^2-20x-4x^2+3x+4x+3=0

(4x^2-4x^2)+(-20x+3x+4x)+3=0

 13x+3 = 0

13x=-3

x=-3/13

b,

(3x-4)(x-2)-3x(x-9)+3=0

3x^2-6x-4x+8 - 3x^2+27x+3=0

(3x^2-3x^2)+(-6x-4x+27x)+(8+3)=0

17x+11=0

17x=-11

x=-11/17

c, 2(x+3)-x^2-3x=0

2(x+3) - x(x+3)=0

(x+3)(2-x)=0

TH1: x+3 = 0; x=-3

TH2: 2-x=0;x=2

 

 

2 tháng 8 2023

`a, 1/2 +x=3/4`

`=> x= 3/4 -1/2`

`=> x= 3/4-2/4`

`=>x= 1/4`

`b, 5/2 -x=1/3`

`=> x= 5/2 -1/3`

`=> x= 15/6 - 2/6`

`=>x= 13/6`

`c, 2 . (1/3 +x)=1/5`

`=> 1/3 +x=1/5:2`

`=> 1/3 +x= 1/10`

`=>x= 1/10-1/3`

`=>x= 3/30 - 10/30`

`=>x=-7/30`

`d, 2/3 - (1/2 -x)=1/5`

`=> 1/2-x= 2/3 -1/5`

`=>1/2-x= 10/15 - 3/15`

`=>1/2-x=7/15`

`=>x= 1/2-7/15`

`=>x=1/30`

2 tháng 8 2023

`1/2 + x = 3/4`

`=>    x  = 3/4 - 1/2`

`=>    x   = 1/4`

`5/2 - x  = 1/3`

`=>    x  =  5/2 - 1/3`

`=>    x  = 13/6`

`2.(1/3 + x) = 1/5`

`=>1/3 + x  = 1/10 `

`=>         x =  1/10 - 1/3`

`=>        x   = -7/30`

`2/3 - (1/2 -x)= 1/5`

`=>     1/2 - x = 7/15`

`=>             x  = 1/2 - 7/15`

`=>             x  = 1/30`

a: Ta có: \(\left(x+2\right)\left(x+3\right)-\left(x-2\right)\left(x-5\right)=-4\)

\(\Leftrightarrow x^2+5x+6-x^2+7x-10=-4\)

\(\Leftrightarrow12x=0\)

hay x=0

b: Ta có: \(\left(x+1\right)\left(x^2-x+1\right)-x\left(x-3\right)\left(x+3\right)=8\)

\(\Leftrightarrow x^3+1-x^3+9x=8\)

\(\Leftrightarrow9x=7\)

hay \(x=\dfrac{7}{9}\)

c: Ta có: \(4x^2-9=\left(3x+1\right)\left(2x-3\right)\)

\(\Leftrightarrow\left(3x+1\right)\left(2x-3\right)-\left(2x-3\right)\left(2x+3\right)=0\)

\(\Leftrightarrow\left(2x-3\right)\left(3x+1-2x-3\right)=0\)

\(\Leftrightarrow\left(2x-3\right)\left(x-2\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{3}{2}\\x=2\end{matrix}\right.\)